Spectral, Theoretical and Biological Studies of 3-((4-Mercaptophenyl)imino)-1-phenylindolin-2-one Schiff Base and Its Organotellurium(IV) Complexes - Kumar, Manish; Jangra Darolia, Poonam; Antil, Nidhi; Dalal, Mahak; Narwal, Jitender; Verma, K.K.; Garg, Sapana (Asian Journal of Chemistry, 2021)
Schiff base ligand (3-((4-mercaptophenyl)imino)-1-phenylindolin-2-one) of 1-phenylindoline-2,3-dione and 4-aminothiophenol was synthesized by refluxing. Organotellurium(IV) complexes of type (RTeCl3.NPhIATP and R2TeCl2.NPhIATP, where R = 4-hydroxyphenyl, 4-methoxyphenyl and 3-methyl-4-hydroxyphenyl, NPhIATP = Schiff base ligand). The ligand and its organotellurium(IV) complexes (9a-f) were characterized by FT-IR, molar conductance, elemental analyses, UV-vis, mass, 1H & 13C NMR spectral studies. Geometry of all the compounds were optimized and octahedral geometry have been proposed for all the tellurium(IV) complexes. Molecular docking was studied to find the binding interactions between ligand (NPhIATP) and receptor proteins: E. coli (3t88) and S. aureus (3ty7). The antimicrobial activity of ligand and its tellurium(IV) complexes have been screened against bacteria and fungi. All the organotellurium(IV) complexes complexes showed good activity to ligand towards different studied microorganisms.